The use of people rank technique for data dissemination in opportunistic network - Donna, Christen George (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Communication has been a great deal in today's society. In Opportunistic Network (OppNet), mobile devices forward messages .without the need of an end-to-end infrastructure. The question is which forwarding algorithm offers the best balance between number of successful messages forwarded and the time it takes to forward the message. In this paper, we are going to develop on one of the forwarding algorithm, People Rank algorithm, which is a social-based forwarding algorithm. Inspired ·by PageRank algorithm, this algorithm gives higher weight to nodes if they are socially connected to other popular nodes of the network. In order to understand how the nodes are ranked and how the messages are forwarded, we develop a simulation-based approach using ONE simulator. The experiment parameters are manipulated to study the behavior of the nodes in different environment. Through the research and experiment, we are able to compare PeopleRank algorithm with other forwarding algorithms and come out with the best forwarding algorithm in Opportunistic Network